Numerical study on ignition amelioration of a hydrogen-enriched Wankel engine under lean-burn condition. (1st December 2019) - Shi, Cheng; Ji, Changwei; Ge, Yunshan; Wang, Shuofeng; Bao, Jianhui; Yang, Jinxin
Highlights: A simulation model of the hydrogen-enriched Wankel engine was built and validated. Single-spark ignition strategies consist of split ignition, high-energy ignition. Twin-spark ignition strategies cover asynchronous ignition and energy allocation. The preferable arrangement of the twin spark plug was T/L = 1.5. Optimal combustion was gained as the leading plug was ignited earlier and stronger. Abstract: For the hydrogen-enriched spark-ignited Wankel engine, the optimization of ignition strategy is conducive to improve combustion performance and specifically effective to lessen the unburned region due to the elongated rotor chamber. In this paper, the role of the number of the ignition source, twin-spark plug location, asynchronous ignition, and energy allocation in improving lean combustion was investigated through the three-dimensional computational fluid dynamics model coupling with kinetic mechanisms. The model was validated by experiment, and good agreements between measured and predicted combustion pressure and the heat release rate was obtained. Results showed that the improvements of engine combustion were limited by single-spark ignition strategies, and the twin-spark ignition configuration was capable of enhancing combustion efficiency drastically. The arrangement of the twin-spark plug determined the space for flame development, and it was favorable for the trailing plug to stand a greater offset from the minor axis of the engine. An earlier leading-spark ignition enabled flame propagation faster and occurred quenching rapidly, which contributed to higher pressure-output and better heat-release. The higher energy of leading-spark ignition made the mixture consumption faster, combustion pressure higher, and combustion duration shorter. The optimum strategy on combustion was expressed as follows: the location of trailing-spark plug is offset from the minor axis by 20.7 mm; the spark timing and discharge energy of leading-spark plug is 325°EA and 0.03 J, respectively; and those of trailing-spark plug is 335°EA and 0.01 J. It was recommended that the leading-spark ignition was set earlier and stronger for practical operations.